Understanding the Employment of Digital Design Tools in Architectural Education in Turkey - Gül , Leman Figen; Çağdaş, Gülen; Gül, Murat; Çağlar, Tayyibe Nur (ICONARCH International Congress of Architecture and Planning, 2014)
With the Global developments and technological advances in the rapidly changing world, some alterations to the higher education system are inevitable. In Turkey, there has been a fast transformation in the higher education system with the establishment of foundation universities and spending of the significant amount of resources. In particular, as of 2013, there are eighty-three design schools offering bachelor of architecture degree in Turkey. There is no evidence of whether those schools offer up-to-date curriculum, which complies with the international standards and contemporary education models. We also do not know how the information and communication technologies, which have the growing impact on architectural education worldwide, are implemented in the curricula. The aim of the paper is: to understand the current architectural curricula in Turkey, to investigate the changing trends in education and to understand the role of advance information and communication technologies in architectural design education. The results of the project can be used to develop models for the future program developments.